[RETRACTED] Hibridity and Cutural Identity Through Jude as a Syrian character in Warga's Novel Other Words For Home - Hakim, Arief Rahman; Nurhusna, Siti Deviana Rahma (Vivid: Journal of Language and Literature, 2022)
This article is retracted due to significant overlap with a previously published work titled "Hybridity and Cultural Identity in Warga's Novel Words for Home" in Muslim English Literature Journal, Volume 1 No. 1 2022.We apologize for any inconvenience this may cause.